THE RATE AND CHARACTERS OF MASKED ARTERIAL HYPERTENSION AND MASKED INEFFECTIVENESS OF HYPERTENSION TREATMENT IN INDUSTRIAL WORKERS ACCORDING TO THE PREVENTIVE EXAMINATION - M. I. Smirnova; E. M. Platonova; A. N. Britov; V. M. Gorbunov; A. D. Deev; Y. N. Koshelyaevskaya (Столичная издательская компания, 2015)
Aim. To study the rate and characters of masked arterial hypertension (HT) and masked ineffectiveness of HT treatment in industrial workers within annual preventive examination.Material and methods. Workers (n=185) with normal office blood pressure (BP) <140 and <90 mm Hg were enrolled into cross-cohort study of industrial workers of large enterprise engaged in activity with harmful and/or dangerous conditions (n=477; mean age 53.2±5.5 years). Standard survey, anthropometry, ambulatory BP monitoring (ABPM), blood chemistry, electrocardiography, and echocardiography were performed. Criteria of masked HT and masked HT in treated subjects were the level of office BP <140 and <90 mm Hg in combination with mean BP during the operational period ≥135 and/or ≥85 mmHg. Patient characters significantly associated with this ratio of office BP and BP during the operational period were considered as features of isolated increase in ambulatory BP level.Results. The rate of masked HT among workers with normal office BP was 10.8%, and masked HT among treated subjects was 34.6%. Workers with masked HT, in contrast to the normotensive workers according to the office BP and ABPM measurements, had a higher left ventricular mass index (in males 129.0±21.2 vs. 109.5±28.8 g/m2, respectively, in women 105.2±43.2 vs. 82.4±25.3 g/m2, respectively, p<0.05), and higher body weight (85.4±13.3 vs. 81.3±10.1 kg, respectively; p=0.05). Treated subjects with masked HT, unlike workers with effective antihypertensive therapy had a higher body weight (89.4±16.1 vs. 85.4±15.8 kg, respectively, p<0.05), higher levels of triglycerides (1.56±0.95 vs. 1.23±0.55 mmol/l, respectively, p<0.01) and uric acid (388.5±89.5 vs. 357.2±84.5 mmol/l, respectively, p<0.05), more prominent left ventricular hypertrophy, lower incidence of ischemic heart disease, but higher number of persons taking ACE inhibitors. Occupation and work features were not characters of the masked HT and masked ineffectiveness of HT treatment.Conclusion. Masked HT and masked HT in treated subjects (masked ineffectiveness of HT treatment) can occur in almost a half of industrial workers with normal office BP. Ambulatory BP measurement methods, especially ABPM, as well as standard risk factors detection are necessary for early revealing of HT phenotypes during preventive examination.